Organized business, political regimes and property rights across the Russian Federation - William Pyle (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
This article explores the inter-relationship of collective action within the business community, the nature of the political regime and the security of firms' property rights. Drawing on a pair of surveys recently administered in Russia, we present evidence that post-communist business associations have begun to coordinate business influence over state actors in a manner that is sensitive to regional politics. A firm's ability to defend itself from government predation and to shape its institutional environment as well as its propensity to invest in physical capital are strongly related to both its membership in a business association and the level of democratization in its region. Of particular note, the positive effect of association membership on securing property rights increases in less democratic regions. The evidence, that is, suggests that collective action in the business community substitutes for democratic pressure in constraining public officials.
URN:NBN:fi:bof-201408072145
Keywords: D7; K4; P48; 330; collective action; property rights; political institutions; business associations